Ionic liquids functionalized Î²-cyclodextrin polymer for separation/analysis of magnolol - Nan Zhou; Xia-Shi Zhu (Elsevier, 2014)
Ionic liquids functionalized Î²-cyclodextrin polymer, a mono-6-deoxy-6-(1,2-dimethylimidazolium)-Î²-cyclodextrin iodide polymer (ILs-Î²-CDCP), was synthesized as a solid-phase adsorbent coupled with high-performance liquid chromatography for separating or analyzing magnolol in drug samples. The results showed that magnolol was adsorbed rapidly on ILs-Î²-CDCP and eluted with methanol. Under the optimum conditions, preconcentration factor of the proposed method was 12. The linear range, limit of detection (LOD), correlation coefficient (R) and relative standard deviation (RSD) were found to be 0.02â8.00Â Î¼g/mL, 1.9Â ng/mL, 0.9992 and 2.76% (n=3, c=2.00Â Î¼g/mL), respectively. The interaction between ILs-Î²-CDCP and magnolol was studied through the inclusion constant, FTIR and TGA analysis. This proposed method has been successfully applied to the determination of magnolol in real samples. Keywords: Magnolol, Ionic liquids functionalized-Î²-cyclodextrin polymer, Solid-phase extraction, High-performance liquid chromatography